(untitled) (Bangladesh Journal of Urology, 2020)
Introduction: Female urethral stricture is a difficult issue in Urology. Many of the times it may follow any sort of urethral instrumentation but in other cases no definite precipitating causes are unidentified. Methods: This was a prospective study. The sample size was n – 50. All cases were recurrent with the history of urethral dilatations, urethrotomies in multiple sessions. The diagnostic investigations in VCUG (voiding cystourethrogram), Ultrasound scan of kidney Ureter, bladder with post void residues, Uroflometry etc. Due to limitations, Urodynamic study was done in limited cases. Urethral augmentation was done using dorsal substitution of OMG (oral mucosal graft). Urethral catheter was left for 03 – 04 weeks. Results: After removal of catheter, urinary flow was observed; excellent in all the cases. It remain satisfactory in 06 months of follow-up. Overall result is excellent. Conclusions: Female urethral stricture is a difficult issue in Urology, Urethral dilatation, urethrotomies, clean intermittent catheterization are good options but need frequent procedures. Urethral augmentation with dorsal substitution of oral mucosal graft is a curative approach in long-run. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.158-163